Resin composite plus connective tissue graft to treat single maxillary gingival recession associated with non-carious cervical lesion: Randomized clinical trial - Santamaria, Mauro Pedrine [UNESP]; Queiroz, Lucas Araújo; Mathias, Ingrid Fernandes [UNESP]; Neves, Felipe Lucas Da Silva [UNESP]; Silveira, Camila Augusto [UNESP]; Bresciani, Eduardo [UNESP]; Jardini, Maria Aparecida Neves [UNESP]; Sallum, Enilson Antônio (Wiley, 2016)
Aim To evaluate clinically, the aesthetics and the patient-centred parameters after the treatment of gingival recession associated with non-carious cervical lesion by connective tissue graft alone or combined with a nanofilled resin composite restoration. Methods Thirty-six patients presenting one Miller Class I or II gingival recessions and B+ tooth cervical defect were included. The defects were treated by either connective tissue graft (CTG: control group; n = 18) or connective tissue graft plus resin composite restoration (CTG+RC: test group; n = 18). Results The mean percentage of defect coverage was 82.16 ± 16.1% for CTG and 73.84 ± 19.2% for CTG+RC after 1 year (p > 0.05). Both groups presented statistically significant improvements in two aesthetics evaluations. The professional evaluation (MRES) was 7.44 ± 2.3 for the CTG group and 7.52 ± 2.27 for CTG+RC after 1 year, with no significant difference between the groups. The two groups presented significant reduction of dentin sensitivity (DS), it decreased from 94.4% of the sites to 44.4% in the CTG group and from 88.8% to 5.5% in the CTG+RC group. Conclusions CTG or CTG+RC can successfully treat gingival recession associated with B+ non-carious cervical lesion, but less sensitivity may be expected with the combined approach (NCT02423473).
Keywords: gingival recession; tooth abrasion; tooth cervix